Effect of Mucograft® seal on Post-extraction Ridge Preservation Using Bone Allograft: A Randomized Controlled Clinical Trial and Radiographic. - Natto, Zuhair. (2017)
Abstract: Background/ Objective: One of the serious consequences of single or multiple tooth extraction is the bone resorption that follows, which may create aesthetic problems and compromise future implant placement. Therefore, it is important to preserve as much bone and soft tissue as possible at the time of the extraction to maintain aesthetics, allow the placement of dental implants in a prosthetically ideal position, and prevent future invasive, expensive, and time consuming procedures. The aim of this prospective, controlled, randomized, parallel arm study was to compare clinically and radiographically the hard and soft tissue remodeling 4 months following alveolar ridge preservation (ARP) in extraction sockets using a collagen matrix, Mucograft Seal ® (MS) or collagen sponge (CS) as barriers, in combination with freeze dried bone allograft (FDBA). Materials and methods: Participants were assigned to one of the two groups at the day of the extraction and ARP using a computer-generated randomization scheme. Subjects were blinded to which treatment group they were assigned to. Sectional cone beam computed tomographies (CBCTs) were de-identified. The clinical and radiographic measurements for hard and soft tissues were performed with the same stent for standardization and recorded at two different times: 1) Before extraction, 2) 4 months after healing. The flapless technique following atraumatic extraction was used for the two types of barriers. Independent sample t test, paired t test, ANCOVA, Chi-square, Fisher exact tests, regression analysis and intraclass correlation were performed. All statistical analysis was blinded. The groups were exposed after all the analyses were conducted. The report of this clinical trial conforms to the CONSORT statement. Results: Twenty-eight patients completed the study with no drop outs, 14 in the MS group and 14 in the CS group. No significant differences between the two groups were detected for demographic characteristics and all soft and hard tissue measurements at baseline with the exception of Distance between Vertical Reference Point and Palatal (Lingual) Crest (VR-PC) which was significantly greater in the CS than the MS group. A slight (0.9 mm) but significantly greater increase from baseline (p=0.01) in gingival thickness at the coronal part was observed in the MC group compared to the CS group (0.5 mm). Horizontal bone loss in the coronal part was less in the MS group (1.21 mm, 14.91%) than in the CS group(1.47 mm, 20.40%). Decrease in bone width of 0.90 and 0.54 mm (10.22 % and 5.94 %) in the MS group and 0.96 and 0.57mm (11.74% and 6.94%), in the CS group was recorded at the 7, and 10 mm reference points respectively in the radiographic measurements with no significant differences between groups. Vertical bone resorption was observed in both groups (0.30 mm in the buccal and 0.27 mm in the palatal in the MS group and 0.79 and 0.49 mm in the CS group, respectively) with no significant difference between groups. More crestal bone resorption occurred on the buccal than on the palatal aspect in both groups. Radiographic bone quality evaluation indicated that the majority of sites presented Type I, II or III in both groups ( 57% in the CS and 71% in the MS group )without significant differences between groups. No significant effect on the clinical parameters (probing depth, clinical attachment level, and recession) was detected on the adjacent teeth following extraction and ARP in both groups. Conclusions: When combined with FDBA, both collagen matrix and collagen sponge are effective in maintaining soft tissue thickness, and minimizing ridge resorption in all dimensions, in sockets with a buccal loss of <2mm in comparison to previously reported findings recorded after tooth extraction without ARP. The MS was more effective in increasing crestal soft tissue thickness than the CS. Adequate radiographic bone quality for implant placement was observed in the majority of sites in both groups.; Thesis (M.S.)--Tufts University, 2016.; Submitted to the Dept. of Periodontology.; Advisor: Y. Natalie Jeong.; Committee: Andreas Parashis, Bjorn Steffensen, Rumpa Ganguly, and Matthew Finkelman.; Keyword: Dentistry.